2020
DOI: 10.1111/anu.12991
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous multienzyme complex supplementation in diets on growth performance, digestive enzyme activity and non‐specific immunity of the Japanese seabass,Lateolabrax japonicus

Abstract: This experiment aimed to investigate the effects of exogenous multienzyme complex (EC) on growth performance, digestive enzyme activity and non‐specific immunity of the Japanese seabass, Lateolabrax japonicus (initial weight 27.09 ± 0.08 g). EC includes protease, xylanase, glucanase and mannase. Japanese seabass were given six levels of EC (0, 0.5, 1.0, 1.5, 2.0 and 2.5 g/kg) for 28 days. Results show that EC significantly enhanced the weight gain rate and specific growth rate (p < .05), while the feed convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 55 publications
(72 reference statements)
0
5
0
1
Order By: Relevance
“…It can also eliminate the anti-nutrient factor in feed, improve digestive function and enhance the immune resistance of aquatic animals. Enzyme preparation has been widely used in the fish feed industry [62,63]. To date, there have been no reports relevant to application of enzyme preparation on E. sinensis.…”
Section: Energy Metabolism and Homeostasis Maintenance After Feeding ...mentioning
confidence: 99%
“…It can also eliminate the anti-nutrient factor in feed, improve digestive function and enhance the immune resistance of aquatic animals. Enzyme preparation has been widely used in the fish feed industry [62,63]. To date, there have been no reports relevant to application of enzyme preparation on E. sinensis.…”
Section: Energy Metabolism and Homeostasis Maintenance After Feeding ...mentioning
confidence: 99%
“…A diferença no tempo entre os picos de excreção pode ser atribuída ao sinergismo entre enzimas quando adicionadas nas rações como blends ou complexos, pois, segundo Oliveira et al (2007), a adição combinada de enzimas digestivas permite que estas atuem de forma simultânea e complementar possibilitando aumento na disponibilidade de nutrientes. Esta interação pode ser identificada na pesquisa desenvolvida por Huang et al (2020) onde ao avaliarem a eficiência de um complexo enzimático composto por protease, xilanase, glucanase e manase em dietas para robalo japonês, observaram aumento na atividade da enzima lipase.…”
Section: Taxa De Excreção De Amôniaunclassified
“…The multienzyme complex (MEC) is composed of one or several single enzymes as the main component, mixed with other single enzyme preparations, or obtained by the fermentation of one or more microorganisms [4]. It has been reported that supplementation with exogenous enzyme preparations offsets the negative effects of removing antibiotics from animal diets [5].…”
Section: Introductionmentioning
confidence: 99%